Systematic review of outcomes after distal pancreatectomy with coeliac axis resection for locally advanced pancreatic cancer. Issue 8 (15th June 2016) - Klompmaker, S; de Rooij, T; Korteweg, J J; van Dieren, S; van Lienden, K P; van Gulik, T M; Busch, O R; Besselink, M G
Abstract: Background: Pancreatic cancer involving the coeliac axis is considered unresectable by most guidelines, with a median survival of 6–11 months. A subgroup of these patients can undergo distal pancreatectomy with coeliac axis resection, but consensus on the value of this procedure is lacking. The evidence for this procedure, including the impact of preoperative hepatic artery embolization and (neo)adjuvant therapy, was evaluated. Methods: A systematic review was performed according to the PRISMA guidelines until 27 May 2015. The primary endpoint was overall survival; secondary endpoints included morbidity and radical resection rates. Results: A total of 19 retrospective studies, involving 240 patients, were included. The methodological quality of the studies ranged from poor to moderate. A radical resection was reported in 74·5 per cent (152 of 204), major morbidity in 27 per cent (26 of 96), ischaemic morbidity in 9·0 per cent (21 of 223) and 90-day mortality in 3·5 per cent (4 of 113). Overall, 35·5 per cent of patients (55 of 155) underwent preoperative hepatic artery embolization without an apparent beneficial impact on ischaemic morbidity. Overall, 15·7 per cent (29 of 185) had neoadjuvant and 51·0 per cent (75 of 147) had adjuvant therapy. There was a difference in survival between patient series where less than half of patients had (neo)adjuvant chemotherapy and series where more than half were receiving this treatment: case-weighted median overall survival was 16 (range 9–48) versus 18 (10–26) months respectively ( P = 0·002). Overall median survival for the whole study population was 14·4 (range 9–48) months. Conclusion: Distal pancreatectomy with coeliac axis resection seems a valuable option for selected patients with pancreatic cancer involving the coeliac axis with acceptable morbidity and mortality, and a median survival of 18 months when combined with (neo)adjuvant therapy. Abstract : Technically feasible in selected patients